Adoption of food safety practices in milk production: Implications for dairy farmers in India - Kumar, Anjani; Wright, Iain A.; Singh, D.K. (Informa UK Limited, 2011)
This study investigates the status, estimates the cost, and identifies the determinants of compliance with food safety measures in milk production in India. The study is based on the cross section primary data collected at the farm level in 3 states of India, namely, Bihar, Punjab, and Uttar Pradesh, in the year 2007. These states capture the geographical and institutional diversity of milk production and marketing in the country. The study shows that the status of compliance with food safety measures at the dairy farm level is not encouraging and a lot of efforts are needed to bridge this gap. The adoption intensity of food safety practices shows wide inter- and intraregional variations. This intensity depicts a positive relationship with herd size. The additional cost of compliance with food milk safety measures reveals an inverse relationship with herd size. The adoption intensity of food safety practices has been found to be influenced by the dairy farmers' characteristics. Herd size, education level, expertise in dairying, and integration of dairy farmers with modern milk supply chain have positive influence on the adoption intensity of food safety practices at the farm level. The positive relationship between adoption intensity of food safety measures and farmers' realization of milk price would influence farmers for greater adoption of these measures.